PENGARUH PEMBENTUKAN PERILAKU CARING BERBASIS STIMULUS – ORGANISME – RESPON (SOR) TERHADAP PERILAKU CARING MAHASISWA KEPERAWATAN - Palupi, Niken WN; Ikaningtyas, Nurlia (STIKES Bethesda Yakkum, 2018)
Background: The current wave of healthcare marketing has changed from the era of service excellence based on standard operational procedures or also minimal service standards shifted to the era of carewith character that makes caring values the core of healthcare. The formation of caring nursing behavior begins in nursing education. The formation of caring behaviour is very diffcult to do because of diversity in student’s background. Therefore the authors are interested in investigating the in?uence of formation of caring behavior based on Stimulus - Organism - Response to caring behavior of nursing students of Stikes Bethesda Yakkum Yogyakarta. Method: This study used pre-experiment one group pretest-posttest research design. The population in this study was all students of semester IV of Stikes Bethesda Yakkum Yogyakarta academic year 2016/2017 amounted to 31 students. Sample selection in this research was done with non-probability sampling that was purposive sampling. To know the in?uence between two variables (dependent and independent variable) bivariate analysis was performed. The statistical test for all analysis above was analyzed with signifcance level 95% (?: 0,05). The test used was paired t-test. Result: The result shows in?uence of caring behaviour based on SOR on caring behaviour of student of nursing with P value: 0,00. Conclusion: The formation of caring behavior based on SOR has an in?uence on caring behavior of students but students also realize there are still some behaviours that need to be developed based on 10carative values by Jean Watson.Keywords: Caring - Stimulus - Organisme - Respon